The Influence of Environmental Pollution Knowledge on the Behavior of Using Single-Use Plastic Items among Students of the Faculty of Teacher Training and Education, Pattimura University, Ambon - Rahanyamtel, Muhamad Yahya; Pinoa, Wiclif Sephnath; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study investigates the impact of knowledge about environmental pollution on the behavior of single-use plastic use in academic environments, specifically at the Faculty of Teacher Training and Education, Pattimura University, Ambon. Involving students of the social science education program, the study used a survey approach with data collected from September 11 to October 11, 2023. Knowledge was measured using the Guttman scale, while the behavior of single-use plastic use was evaluated through a Likert questionnaire. The analysis showed a significant relationship between knowledge about environmental pollution and students' behavior of single-use plastic use. Although most respondents had adequate knowledge, the use of single-use plastic was still high, highlighting the need to improve sustainable practices. Regression analysis strengthened this finding by confirming the significant influence between knowledge and behavior. Recommendations include developing more intensive education programs and campaigns on the negative impacts of single-use plastics and providing environmentally friendly alternatives. Collaboration between educational institutions, government, and the community is expected to create a more sustainable environment.